(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides a detailed exploration of verbs and their grammatical categories, offering insights into the critical role verbs play in language structure and meaning. It discusses key grammatical categories such as tense, aspect, mood, voice, person, number, and transitivity, illustrating how these elements define a verb’s form and function. The article also highlights the significance of auxiliary and modal verbs, the process of inflection and conjugation, and the challenges posed by irregular verbs. With its clear structure